2024
DOI: 10.1590/2175-8239-jbn-2022-0116en
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of atherosclerosis and endothelial dysfunction risk factors in patients with primary glomerulonephritis

Abstract: Introduction: Glomerulonephritis are the third cause of chronic kidney disease (CKD) requiring dialysis in Brazil. Mineral and bone disorder (MBD) is one of the complications of CKD and is already present in the early stages. Assessment of carotid intima-media thickness (CIMT) and flow-mediated vasodilatation (FMV) are non-invasive ways of assessing cardiovascular risk. Hypothesis: Patients with primary glomerulonephritis (PG) have high prevalence of atherosclerosis and endothelial dysfunction, not fully expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…As part of the conclusion, the study by Hageman et al 3 found a significant inverse correlation between FMV and serum uric acid in the PG group, although Patients with glomerular disease and proteinuria may exhibit increased risk for cardiovascular disease, in part due to traditional risk factors such as associated hypertension, dyslipidemia, age, gender, and occasional obesity. In addition, it has been well documented that more advanced stages of chronic kidney disease (CKD) that may occur in cases of primary glomerulonephritis (PG), are associated with several nontraditional risk factors.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…As part of the conclusion, the study by Hageman et al 3 found a significant inverse correlation between FMV and serum uric acid in the PG group, although Patients with glomerular disease and proteinuria may exhibit increased risk for cardiovascular disease, in part due to traditional risk factors such as associated hypertension, dyslipidemia, age, gender, and occasional obesity. In addition, it has been well documented that more advanced stages of chronic kidney disease (CKD) that may occur in cases of primary glomerulonephritis (PG), are associated with several nontraditional risk factors.…”
mentioning
confidence: 83%
“…As part of the conclusion, the study by Hageman et al 3 found a significant inverse correlation between FMV and serum uric acid in the PG group, although information regarding serum uric acid levels in PG and control groups are lacking. The mechanisms of hyperuricemia-mediated endothelial dysfunction were recently reviewed by Wei et al 8 and include decreased nitric oxide production, oxidative stress, epithelial-to-mesenchymal transition, endothelial cell insulin resistance, and activation to release inflammatory cytokines.…”
mentioning
confidence: 84%
See 3 more Smart Citations